2009
DOI: 10.1186/1479-0556-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with cyclophosphamide and DNA preparation inhibits the tumor growth in mice

Abstract: Background: When cyclophosphamide and preparations of fragmented exogenous genomic double stranded DNA were administered in sequence, the regressive effect on the tumor was synergic: this combined treatment had a more pronounced effect than cyclophosphamide alone. Our further studies demonstrated that exogenous DNA stimulated the maturation and specific activities of dendritic cells. This suggests that cyclophosphamide, combined with DNA, leads to an immune response to the tumors that were grafted into the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…Analysis of activation of adaptive immune response by dsDNA preparations revealed that immune system contribution accounted for only partial Krebs-2 transplant regression 18 , 19 . At the same time, we showed that synergistic action of CP and dsDNA may alter hematopoietic stem cells so that some of their pluripotency properties are lost 15 , 16 …”
Section: Resultsmentioning
confidence: 99%
“…Analysis of activation of adaptive immune response by dsDNA preparations revealed that immune system contribution accounted for only partial Krebs-2 transplant regression 18 , 19 . At the same time, we showed that synergistic action of CP and dsDNA may alter hematopoietic stem cells so that some of their pluripotency properties are lost 15 , 16 …”
Section: Resultsmentioning
confidence: 99%
“…Proceeding on reported observations [14,39,47], we assumed that this inhibition may be due to the inducer effect of dsDNA on DC maturation in vivo that causes effective presentation of antigens of tumor lysate and activates antitumor mechanisms of the adaptive immunity.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic effect is synergic in that cytostatic preferentially decreases the amount of regulatory T cells in the tumor microenvironment and/or directly kills tumor cells, while dsDNA preparation stimulate maturation and activity of cells of the adaptive immunity [9,39]. …”
Section: Introductionmentioning
confidence: 99%
“…Пятая серия экспериментов В этой серии экспериментов была предпринята попытка объединить в одной группе описанные эффективные режимы и препараты. Одновременно были сформированы группы, в терапию которых была введена обработка мышей препаратом «Панаген» в режиме, активирующем развитие противоракового АИ (Alyamkina et al, 2009(Alyamkina et al, , 2010a(Alyamkina et al, -c, 2012. Также животным проводили регламентированную пересадку ККМ (рис.…”
Section: Discussionunclassified
“…AI -adaptive immunity activation (Alyamkina et al, 2009(Alyamkina et al, , 2010a Принципиально можно было предположить несколько возможностей индукции развития ракового (но не связанного с СВР или иным) асцита после обработки препаратом дцДНК, когда на СИРК не оказывается терапевтического элиминирующего воздействия: 1) признак интернализации дцДНК, являющийся причиной разрушения туморогенного начала предполагаемых СИРК в синергизме с ЦФ, характерен не для СИРК, а для их коммитированных потомков, а значит, причинная клетка остается интактной; 2) не вся популяция СИРК в силу биологических особенностей в один и тот же момент времени способна интернализовать фрагменты дцДНК и, следовательно, избежать синергической элиминации; 3) возможно, что, как показано в работе (Dolgova et al, 2013) на стволовых клетках крови, СИРК также могут на время терять туморогенность, а затем восстанавливать ее; 4) развитие вторичного асцита также может быть связано с тем, что в определенных случаях не все СИРК «асцитного бульона» разрушаются или меняют свой раковый статус. Это возможно в том случае, когда проведенные обработки не перекрыли в полной мере промежуток времени разрешения интермедиатов, в тече ние которого происходит интерференция репаратив ного процесса с последующим разрушением или клетки, или ее свойств, например отрезок времени между 12 и 18 ч; 5) известно, что раковые клетки способны к реверсивному перерождению, что означает, что коммитированная раковая клетка в силу определенных причин способна вернуться к фенотипу СИРК (Gupta et al, 2011); 6) возможна ситуация генетической трансформации (генометастазирование) стволовых клеток организма мыши генетическим материалом огромного числа погибших раковых клеток асцита Кребс-2 (Garcia-Olmo et al, 2000).…”
Section: Discussionunclassified